STRATEGI PENGEMBANGAN PRODUK SENDRATARI RAMAYANA PRAMBANAN YOGYAKARTA - , SHOLIHIN DUNAMAR L. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to determine what products are owned Ramayana and the preparations made in the face of world tourism, given the development of the modern era. In this paper also discussed a bit about the technology needs to be developed for better lighting during gigs, given the course of the show often outdoors (Open Air). Operational and dancers very big impact on the success rate of a high-value performance. Better working procedures need to be constantly improved to achieve maximum satisfaction of the travelers. In daily activities, Ramayana did not escape from a variety of problems or complaints from tourists, but the issue can be addressed properly by the employees to provide special tips in accordance with service standards that have been defined of Ramayana Ballet.